Isolation, identification and antifungal susceptibility of Candida in patients with fungal sepsis - Wani, Bilal Ahmad; Lone, Mohd Rafiq; Saqib, Najmus (International Journal of Research in Medical Sciences, 2019)
Background: In this study, our aim was to identify and isolate Candida species from patients admitted in ICU,s of our hospital and to determine their susceptibilities to various antifungal agents so as to find the local resistance pattern and guide for empirical treatment. Methods: In our study 37 strains of candida were isolated (4 Candida albicans, 33 Non-albicans Candida strains). Candida species were identified by conventional, biochemical and molecular methods. Antifungal susceptibility tests for amphotericin B, fluconazole, itraconazole, ketoconazole and voriconazole were performed with broth microdilution method and E- tests as described by National Committee for Clinical Laboratory Standards (NCCLS). Results: Out of 37 Candida strains, the most prevalent species were C. tropicalis (43.2%), C. parapsilosis (24.3%), C. krusei (16.2%), C. albicans (10.8%), and C. glabrata (2.7%). Among all strains four strains (10.8 %) were resistant, two Candida albicans where found resistant to fluconazole one Candida krusei and one Candida parapsilosis were found to be resistant to all azoles. Conclusions: Candidemia continues to be associated with substantial morbidity and mortality and non albicans Candida species are the commonly isolated pathogen from those patients admitted in tertiary care hospitals in Indian scenario. Thus, it is imperative to perform antifungal susceptibility to select appropriate and effective antifungal therapy.